Leukocyte Beta-Catenin Expression Is Disturbed in Systemic Lupus Erythematosus - Orme, Jacob J.; Du, Yong; Vanarsa, Kamala; Wu, Tianfu; Satterthwaite, Anne B.; Mohan, Chandra (PloS one, 2016)
Wnt/β-catenin signaling is relatively understudied in immunity and autoimmunity. β-catenin blocks inflammatory mediators and favors tolerogenic dendritic cell (DC) phenotypes. We show here that leukocytes from lupus-prone mice and SLE patients express diminished β-catenin transcriptional activity, particularly in myeloid cells, although other leukocytes revealed similar trends. Serum levels of DKK-1, an inhibitor under transcriptional control of Wnt/β-catenin, were also decreased in lupus-prone mice. Surprisingly, however, preemptive deletion of β-catenin from macrophages appears to have no effect on lupus development, even in mice with varying genetic loads for lupus. Although myeloid-specific loss of β-catenin does not seem to be important for lupus development, the potential role of this transcription factor in other leukocytes and renal cells remain to be elucidated.